Groundwater level fluctuation caused by tide and groundwater pumping in coastal multi-layer aquifer system - Guo, Qiaona; Liu, Jinhui; Zhu, Xufen; Dai, Yunfeng (Frontiers in Marine Science, 2024)
This paper considered the groundwater head fluctuation induced by tide and pumping in the coastal multi-layered aquifer system. The multi-layered aquifer system comprises an unconfined aquifer, an upper confined aquifer, and a lower confined aquifer. An aquiclude exists between each two aquifers. All the layers terminate at the coastline. The new analytical solutions describing groundwater head variation in the coastal multi-confined aquifer system are derived. Superposition principle and image methods are used for the derivation of the analytical solutions. Analytical solutions of different situations of without considering pumping, of without considering tidal effect, and of N-layered confined aquifers are also derived. The impacts of the parameters of the initial phase shift of tide, pumping rate, position of the pumping well, storage coefficient, and transmissivity on the groundwater head fluctuation are discussed. The analytical solutions are applied with application examples in fitting field observations and parameter estimations. The estimated values of the hydraulic conductivities in the upper and lower confined aquifers are within the range of the values obtained from the field experiments. The fitted results of the analytical solutions capture the main characteristics of groundwater head fluctuation affected by the tide and groundwater pumping. The study of groundwater head fluctuation in the coastal zone is helpful to understand the mechanism of seawater intrusion under the influence of tide and groundwater pumping.